Drug resistance mechanisms in Japanese anaplastic lymphoma kinase‐positive non–small cell lung cancer and the clinical responses based on the resistant mechanisms. Issue 3 (8th February 2020) - Yanagitani, Noriko; Uchibori, Ken; Koike, Sumie; Tsukahara, Mika; Kitazono, Satoru; Yoshizawa, Takahiro; Horiike, Atsushi; Ohyanagi, Fumiyoshi; Tambo, Yuichi; Nishikawa, Shingo; Fujita, Naoya; Katayama, Ryohei; et al.
Abstract: The treatment for anaplastic lymphoma kinase (ALK)‐positive lung cancer has been rapidly evolving since the introduction of several ALK tyrosine kinase inhibitors (ALK‐TKI) in clinical practice. However, the acquired resistance to these drugs has become an important issue. In this study, we collected a total of 112 serial biopsy samples from 32 patients with ALK‐positive lung cancer during multiple ALK‐TKI treatments to reveal the resistance mechanisms to ALK‐TKI. Among 32 patients, 24 patients received more than two ALK‐TKI. Secondary mutations were observed in 8 of 12 specimens after crizotinib failure (G1202R, G1269A, I1171T, L1196M, C1156Y and F1245V). After alectinib failure, G1202R and I1171N mutations were detected in 7 of 15 specimens. G1202R, F1174V and G1202R, and P‐gp overexpression were observed in 3 of 7 samples after ceritinib treatment. L1196M + G1202R, a compound mutation, was detected in 1 specimen after lorlatinib treatment. ALK‐TKI treatment duration was longer in the on‐target treatment group than that in the off‐target group (13.0 vs 1.2 months). In conclusion, resistance to ALK‐TKI based on secondary mutation in this study was similar to that in previous reports, except for crizotinib resistance. Understanding the appropriate treatment matching resistance mechanisms contributes to the efficacy of multiple ALK‐TKI treatment strategies. Abstract : Anaplastic lymphoma kinase (ALK)‐positive lung cancer accounts for 3%–5% of all non–small cell lung cancer cases. The use of ALK tyrosine kinase inhibitors (ALK‐TKI) is highly effective and four ALK‐TKI have been approved in Japan. However, ALK‐TKI lose their efficacy because of acquired resistance. In this study, we analyzed "real world" resistance mechanisms using serial tumor biopsies during sequential treatment with ALK‐TKI in Japanese patients with ALK‐positive lung cancer and revealed the sequential transition of resistance mechanisms. The identification of resistance mechanisms revealed that the precise utilization of ALK‐TKI based on resistance mechanisms will have potential benefits in patients with ALK‐positive lung cancer in clinical settings.